2022
DOI: 10.1111/jonm.13632
|View full text |Cite
|
Sign up to set email alerts
|

High hiring rate of nurses in Catalonia and the rest of Spain hides precarious employment from 2010 to 2019: A quantitative study

Abstract: Aim: This study aims to describe the hiring of nurses in Catalonia and the rest of Spain over 10 years.Background: Precarious employment (PE) has negative consequences for nurses' quality of life and work performance.Methods: Quantitative study using a retrospective, longitudinal, descriptive design.We analysed publicly available employment data from Catalonia and the rest of Spain. Results: Nurses are among the health professionals with the lowest proportion of open-term (permanent) contracts, 25% during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…While medical residents claim that they are offered the possibility of accessing stable interim contracts, the same is not true for nurses, who complain that they do not have the opportunity to access stable contracts. Nurses are among the health professionals with the lowest proportion of permanent contracts, standing at 25% during the first 4 years of employment in Catalonia [ 57 ]. Spain’s precarious employment of nurses and the emigration of nurses to work in other European countries or around the world during the last decades has been well documented in previous studies [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…While medical residents claim that they are offered the possibility of accessing stable interim contracts, the same is not true for nurses, who complain that they do not have the opportunity to access stable contracts. Nurses are among the health professionals with the lowest proportion of permanent contracts, standing at 25% during the first 4 years of employment in Catalonia [ 57 ]. Spain’s precarious employment of nurses and the emigration of nurses to work in other European countries or around the world during the last decades has been well documented in previous studies [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…While medical residents claim that they are offered the possibility of accessing stable interim contracts, the same is not true for nursing, where they complain that they do not have the opportunity to access stable contracts. Nurses are among the health professionals with the lowest proportion of permanent contracts, which stood at 25% during the rst 4 years of employment in Catalonia [41]. Spain's precarious employment of nurses and the emigration of nurses to work in other European countries or around the world during the last decades has been well documented in previous studies [42].…”
Section: Economic and Resource Factorsmentioning
confidence: 85%
“…Temporary contracts have been implemented since the 1970s, showing a strong increase in recent years ( 11 ) . In a Spanish study on the temporary hiring of nurses ( 12 ) , the authors observed that the proportion of workers with a fixed-term contract grew by 38.7% in 2018. Still in the same study, nurses were the healthcare workers with the highest proportion of temporary contracts in the first four years after completing their degree.…”
Section: Discussionmentioning
confidence: 99%